2007
DOI: 10.1007/s12079-007-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of reactive oxygen species in the activation of mitogen‐activated protein kinases and Akt by key receptors on B‐lymphocytes: CD40, the B cell antigen receptor, and CXCR4

Abstract: The differential requirement for ROS in the activation of ERK, JNK, p38, and Akt by the BCR, CD40, and CXCR4 likely reflects the multiplicity of upstream activators for each of these kinases, only some of which may be regulated in a redox-dependent manner. These findings support the idea that ROS are important second messengers in B cells and suggest that oxidants or anti-oxidants could be used to modulate B cell activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 103 publications
(142 reference statements)
1
22
0
Order By: Relevance
“…SDF-1 is a member of the C-X-C chemokine subfamily and the only known ligand for the G protein-coupled receptor CXCR4 [17,18]. It has been shown that CXCR4 is expressed in malignant tumors and the SDF-1/CXCR4 interaction is involved in tumor progression, particularly brain and breast cancers [19]. Binding of SDF-1 to CXCR4 leads to stimulation of intracellular signaling that involves activation of multiple targets, including ERK1/2, MAPK, JNK, and AKT effectors [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…SDF-1 is a member of the C-X-C chemokine subfamily and the only known ligand for the G protein-coupled receptor CXCR4 [17,18]. It has been shown that CXCR4 is expressed in malignant tumors and the SDF-1/CXCR4 interaction is involved in tumor progression, particularly brain and breast cancers [19]. Binding of SDF-1 to CXCR4 leads to stimulation of intracellular signaling that involves activation of multiple targets, including ERK1/2, MAPK, JNK, and AKT effectors [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Upon SDF-1 binding to the CXCR4 receptor, there is a signaling pathway that involves transient production of ROS and the activation of phosphoinositide 3-kinase (PI3K) to eventually promote cell migration and survival. 24,25 Cells in culture increase intracellular ROS within seconds when stimulated with SDF-1. 27 The activation of RAGE increases levels of ROS in the cell 28 and signals mDia1, an intracellular signaling partner to RAGE, which has been implicated in smooth muscle cell migration and expansion.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thus, ROS is a common intracellular messenger in the signaling pathways activated by CXCR4 and RAGE. On the one hand, the ROS spike is integral to the SDF-1 signaling pathway, 24,25 and on the other hand, AGE binding to RAGE increases ROS levels. 28 Since the site of ROS generation in both cases is in the cytosol, 24,28 it is plausible that the two pathways intersect in a negative way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway is triggered by HBO 2 in localized vasculogenic stem cells, which augments VEGF and SDF-1 synthesis, enhancing neovascularization (115,116). Subsequent signaling between SDF-1 and its cognate cellular receptor, CXCR4, also involves ROS (89). Likely a synergistic process, lactate can also mediate HIF stabilization in endothelial cells by metabolic conversion to pyruvate that inhibits prolyl hydroxylases (160).…”
Section: Oxygen and Wound Healingmentioning
confidence: 99%